ANALISIS PERHITUNGAN SISA TULANGAN (WASTE), KEBUTUHAN SERTA BIAYA TULANGAN PADA PROYEK RUMAH SAKIT BUNDA THAMRIN MEDAN - Yudistira Ramadhan, Yudis (Jurnal Media Teknik Sipil Samudra, 2023)
In the implementation of construction, there is such thing as a residual use of material which is commonly referred to as Waste Construction. Errors in the supervision and calculation of materials can have a major impact on the budget spent on project implementation, one of which is the use of reinforcing iron material. The use of reinforcing iron material is very important to be considered and calculated carefully and precisely so that it has very little material remnants. Therefore, the purpose of this research is to find out the amount of reinforcement needed and the required cost along with the reinforcement waste. The method used in this calculation is the Bar Bending Schedule method with the Microsoft Excel program to calculate reinforcement waste and calculate reinforcement requirements for column, beam and floor slab structure work along with the percentage comparison between reinforcement waste and reinforcement requirements. Based on the results of data processing, the need for reinforcement needed for the work of Foundations, Columns, Beams, Floor Plates and Stairs is 183380.233 kg. A lot of waste reinforcement for the work of Foundations, Columns, Beams, Floor Plates and Stairs as much as 26673.281 kg. The percentage of waste reinforcement for Foundations, Columns, Beams, Floor Plates and Stairs is 12.52% and the total cost required is Rp. 2,887,099,791.84.